The Trend of Training Innovations in Indonesia: A Systematic Literature Review - Arsyil Waritsman; Rizal Hatapayo (Jurnal Prajaiswara, 2022)
Introduction/Main Objectives: This study aims to examine training innovations in Indonesia from 2017 to 2022. Background Problems: This literary study of Indonesian training innovations is pivotal because it is essentially related to human resource development, particularly in Indonesia. Moreover, The academic studies in this field are insufficient to give knowledge, so this research was conducted to provide a more general description of Indonesian training innovations. The discussions of training innovations in this article are circulated 1) How the training innovations have been carried out in Indonesia, 2) What the advantages of training innovations are, and 3) How to research approach was carried out in the training innovations conducted in Indonesia. Novelty: Systematically examines in-depth training innovations in Indonesia and provides an overview of the development of training innovations in Indonesia. Research Methods: This research used a systematic literature review. Finding/Results: The result shows that 1) The training innovations in Indonesia varied in two terms, application or software and learning process, 2) The innovations had a positive effect on the participants, and 3) in its development, the studies on training innovations were carried out using some methods which are quantitative, qualitative, mixed, and research and development methods. Conclusion: This literature study provides a comprehensive overview of training innovation in Indonesia and becomes an additional description and reference for further research and possibilities for studies on training innovation worldwide.